The answer is 2.
2x = 2x1
So you follow the usual rule about bring down the exponent and subtract one from it and you get
1*2x0= 2x0=2
Chat with our AI personalities
use the double angle formula for cos(2x) which is: cos(2x)=2cos^2(x)-1 by this relation cos^2(x)=(cos(2x)+1)/2 now we'd integrate this instead this will give sin(2x)/4+x/2 =) hope this helps
Differentiating x^2 can be accomplished by using the Power Rule. This provides that d/dx (x^2)=2x
2x+x is 3x
(2x + 1) + (x*x - 2x + 1) = x^2 + 2x - 2x + 1 + 1 = x^2 + 2
2X * 2X * 2X = 8X^3 2X^3 is saying 2*( X * X * X) = 2X^3